Rising Up, Living On : Re-Existences, Sowings, and Decolonial Cracks - Walsh, Catherine E. (Book collections on Project MUSE., 2023)
"In Rising Up, Living On, Catherine Walsh combines decolonial theory and personal narrative to provide an overview of various Indigenous and Black militant social movements in Latin America from the mid-1990s to the present. Walsh develops "re-existence" and "cracks" as theoretical frameworks to understand how alternative social practices have begun to emerge from below to overturn coloniality and a hegemonic neoliberalism. Walsh shows how those who live in direct relation with the land are not only challenging the sovereignty of the Western nation-state, but also imagining what humanity looks like "after Man." The book places Indigenous epistemic traditions in conversation with the work of feminists of color, like M. Jacqui Alexander and Maria Lugones, as well as with the anticolonial critical theorists like Frantz Fanon"--